2005
DOI: 10.1016/j.icesjms.2005.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Eddy formation on the coast of North Norway – evidenced by synoptic sampling

Abstract: In order to resolve advection, migration, and in situ population dynamics of zooplankton and capelin larvae in a mesoscale physical setting on the coast of North Norway, an extensive field survey was conducted. This paper reports on the physical conditions in the area and lays the basic environmental understanding for the analysis of vital rates of the biological components studied. We used a towed wing (SCANFISH) equipped with sensors and Objective Analysis for interpolation of hydrographic data into continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Fig. 6) Pedersen et al (2005) calculated the relative geostrophical current for the study area (based on den- sity measurements from the CTD on the SCANFISH, see their paper for more details). Their results show the presence of several mesoscale eddies.…”
Section: Zooplankton Size Spectra (Fig 5)mentioning
confidence: 99%
See 4 more Smart Citations
“…Fig. 6) Pedersen et al (2005) calculated the relative geostrophical current for the study area (based on den- sity measurements from the CTD on the SCANFISH, see their paper for more details). Their results show the presence of several mesoscale eddies.…”
Section: Zooplankton Size Spectra (Fig 5)mentioning
confidence: 99%
“…The hydrodynamic conditions are described by Pedersen et al (2005), whose study revealed non-linear mesoscale eddies translating eastward, following the shelf break. Anti-cyclonic eddies contained coastal water, while cyclonic eddies contained oceanic water.…”
Section: Eddiesmentioning
confidence: 99%
See 3 more Smart Citations